Identidades contemporâneas do oeste catarinense no telejornalismo regional - Silva, Franscesco Flávio da (2017)
The present dissertation tries to analyze how two local news programs (re)configure in their contents an identity culture of the West region of Santa Catarina. Produced in Chapecó, Santa Catarina - SC, RicTV's midday news program (affiliated to Record) and RBSTV (affiliated to Rede Globo) are registered in the region and carry in their contents. The scenario of this analysis is in the state of SC, a historical stage of tensions between diverse cultures, which in turn made it impossible to define a unified identity, as a "gaucho", in Rio Grande do Sul, despite controversies. Thus, this work analyzes the elements of the identity culture that constitute in contemporaneity the West of Santa Catarina by texts of Chapecó's television news, verifying the senses present in the media about a region and its subjects. As specific objectives we try to identify elements of the identity culture of the West of Santa Catarina contained in the contents of the television news; Analyze these cultural elements present in television news production; As identity representations in the telejournalism contents of the two transmitters; How does a relationship between culture and identity occur in the television news produced in Chapecó? We start from the theoretical-methodological contribution of the Cultural Studies, for the development of an analytical course based on the structure of feeling of Williams (1997), on the circuit of the culture of Paul Du Gay et al. (1999) and a textual analysis of Casetti and Chio (1999). In the analysis we verify that the news programs direct their strategies around the cultural values and senses of the region. We perceive how news texts, a form of presentation and interviews of television news show patterns that constitute clues to an identity of the West of Santa Catarina, built mainly from the municipality of Chapecó, linked to economic development and the "heroic" past that still reverberates on present. At the same time, the new cultural structures emerging in a scenario of traditions still recent and that today is reached by globalization.